Innovations in Coastline Management With Natural and Nature-Based Features (NNBF): Lessons Learned From Three Case Studies - Palinkas, Cindy M.; Orton, Philip; Hummel, Michelle A.; Nardin, William; Sutton-Grier, Ariana E.; Harris, Lora; Gray, Matthew; Li, Ming; Ball, Donna; Burks-Copes, Kelly; Davlasheridze, Meri; De Schipper, Matthieu; et al. (Frontiers in Built Environment, 2022)
Coastal communities around the world are facing increased coastal flooding and shoreline erosion from factors such as sea-level rise and unsustainable development practices. Coastal engineers and managers often rely on gray infrastructure such as seawalls, levees and breakwaters, but are increasingly seeking to incorporate more sustainable natural and nature-based features (NNBF). While coastal restoration projects have been happening for decades, NNBF projects go above and beyond coastal restoration. They seek to provide communities with coastal protection from storms, erosion, and/or flooding while also providing some of the other natural benefits that restored habitats provide. Yet there remain many unknowns about how to design and implement these projects. This study examines three innovative coastal resilience projects that use NNBF approaches to improve coastal community resilience to flooding while providing a host of other benefits: 1) Living Breakwaters in New York Harbor; 2) the Coastal Texas Protection and Restoration Study; and 3) the South Bay Salt Pond Restoration Project in San Francisco Bay. We synthesize findings from these case studies to report areas of progress and illustrate remaining challenges. All three case studies began with innovative project funding and framing that enabled expansion beyond a sole focus on flood risk reduction to include multiple functions and benefits. Each project involved stakeholder engagement and incorporated feedback into the design process. In the Texas case study this dramatically shifted one part of the project design from a more traditional, gray approach to a more natural hybrid solution. We also identified common challenges related to permitting and funding, which often arise as a consequence of uncertainties in performance and long-term sustainability for diverse NNBF approaches. The Living Breakwaters project is helping to address these uncertainties by using detailed computational and physical modeling and a variety of experimental morphologies to help facilitate learning while monitoring future performance. This paper informs and improves future sustainable coastal resilience projects by learning from these past innovations, highlighting the need for integrated and robust monitoring plans for projects after implementation, and emphasizing the critical role of stakeholder engagement.